PERANCANGAN SISTEM INFORMASI MEDICAL CHECK UP BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER 4 MENGGUNAKAN METODE WATERFALL - Luqmanul Hakiym Maulana; Nuril Lutvi Azizah; Ade Eviyanti (Politeknik Bisnis Indonesia, 2023)
The purpose of this research is to develop a web-based Medical Check-Up information system using CodeIgniter 4 framework and implementing the waterfall development method. This system is designed to facilitate administrative management and provision of medical services to patients. Rsu Al-Islam Hm Mawardi Krian Sidoarjo currently uses manual methods in the administration of medical check-ups, which poses several risks in data processing between hospital units. Therefore, this research is conducted to address these issues. The waterfall method is used for the system development stages, including requirements analysis, design, implementation, testing, and maintenance. The requirements analysis phase involves identifying needs such as patient registration and examination results. System design includes database structure, user interface, and business logic to be implemented in the system. Implementation utilizes the CodeIgniter 4 framework, which provides tools and features for web application development. The results of this research align with the hospital's requirements, including patient registration, recording, and delivery of laboratory, radiology, and doctor examination results, which have been tested using the black box method. It is expected that this developed Medical Check-Up information system can enhance the efficiency of the check-up process, expedite patient examination access, and improve the overall quality of healthcare services.